2013
DOI: 10.1088/0953-2048/26/7/075022
|View full text |Cite
|
Sign up to set email alerts
|

Mean square flux noise in SQUIDs and qubits: numerical calculations

Abstract: The performance of SQUIDs and superconducting qubits based on magnetic flux is degraded by the presence of magnetic flux noise with a spectral density scaling approximately inversely with frequency. It is generally accepted that the noise arises from the random reversal of spins on the surface of the superconductors. We introduce a numerical method of calculating the mean square flux noise 2 from independently fluctuating spins on the surface of thin-film loops of arbitrary geometry. By reciprocity, 2 is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Actual devices will show some degree of asymmetry for the current densities at the wire edges. For example, the SQUID is a closed SC wire loop, so to satisfy the Meissner effect it produces higher current density at the inside wire edge, 32 thus minimizing the value of magnetic field inside the wire. Modifying Eq.…”
Section: Numerical Results and Comparison To Finite Loop Approximatio...mentioning
confidence: 99%
See 3 more Smart Citations
“…Actual devices will show some degree of asymmetry for the current densities at the wire edges. For example, the SQUID is a closed SC wire loop, so to satisfy the Meissner effect it produces higher current density at the inside wire edge, 32 thus minimizing the value of magnetic field inside the wire. Modifying Eq.…”
Section: Numerical Results and Comparison To Finite Loop Approximatio...mentioning
confidence: 99%
“…31 More recently, extensive numerical studies 25,32 showed that these calculations greatly underestimated the value of the flux produced by spins located at the wire surfaces, because they did not take account of the singular nature of the spin's dipole field. Indeed, analytic expressions for the flux noise power that take into account the spin's singular behaviour are still absent from the literature.…”
Section: -24mentioning
confidence: 99%
See 2 more Smart Citations
“…InductEx and the modified FastHenry are freeware modules [15], [18] executed from a console or command prompt in MS Windows, Linux, Mac OS X and Mac Power PC. The magnetic field calculation code that solves equations (3) to (5) at arbitrary coordinates was developed as part of a calculation of mean square flux noise in SQUIDs [17] and is open source [19] Matlab code. Mapping of InductEx output files to the vectors required by the magnetic field calculator is done with the InductEx add-on IDensity [18].…”
Section: Code and Availabilitymentioning
confidence: 99%